Sarah Fish: capstone - Fish, Sarah, artist (Colorado State University. Libraries, 2017)
The artist's statement: Depicting what can not be physically seen has always driven my work. How does one capture a state of mind, an emotion, an illness that can't be seen with the eye? I present three narratives experienced through the mind of one individual. Equipped with a Mamiya 7 and rolls of 120 fujichrome color film, I capture each step in their journey, translating them to chromogenic prints. With masters of the psyche at the forefront, such as Alfred Hitchcock, Duane Michaels, and Francesca Woodman, my hope is to transport you to an alternate state of mind, warping your reality into that of the unfamiliar. To put the viewer in the shoes of another is what I believe the purpose of my art is. To let the viewer experience that which is entirely new and uncharted territory for them, allows them to exercise the action of empathy. For those who relate to the work, and see it as a representation of scenarios they have encountered, it's a warm reminder, that they are not alone, and that they can share in the cathartic experience of seeing representation of things they believed could not be represented.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: capstone; photography; image making